INFECTIONS TRANSMITTED THROUGH THE AIR DROPLET - Kurbonova Muxabbat Xurramovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Annotation: This article explores infections transmitted through airborne droplets, emphasizing their mechanisms, prevalence, and methods of prevention. A detailed analysis of literature, research methodologies, results, and discussions provides insight into controlling and mitigating the spread of airborne diseases. Specific recommendations are presented for both public health authorities and individuals.